Autonomy support enhances performance expectancies, positive affect, and motor learning - Lemos, A.; Wulf, G.; Lewthwaite, R.; Chiviacowsky, S. (Psychology of Sport and Exercise, 2017)
Objectives: According to the OPTIMAL theory of motor learning (Wulf & Lewthwaite, 2016), autonomy support contributes to successful performance and learning in part by enhancing learners' expectancies. The present study was designed to test expectancy-related predictions. Specifically, we examined the effects of practice with autonomy support on learners` self-efficacy, positive affect, and thoughts during practice. Design: Experimental study with two groups. Movement form was assessed in two different experimental phases, supplemented by questionnaire data. Method: Ten-year old children were shown a sequence of 5 ballet positions they were asked to learn: Preparatory position, demi plié, tendu with arms and legs in second position, passé with arms in first position, and elevé with feet in first position. In the autonomy-support (AS) group, participants were able to choose video demonstrations throughout practice, while control (C) group participants were provided with demonstrations based on their yoked counterparts` choices. One day after practice, participants performed in a retention test. Results: The AS group demonstrated greater improvements in movement form during practice and enhanced learning relative to the C group. Furthermore, AS participants had higher self-efficacy and greater positive affect than the C group. Also, AS participants reported having more positive thoughts during practice relative to C group participants, who reported more negative and self-related thoughts. Conclusions: The present findings are in line with OPTIMAL theory predictions. They highlight the motivational underpinnings of the learning benefits that are seen when learners are given choices.